First Record of Myotis occultus (Vespertilionidae) in the State of Guanajuato, Mexico - Magaña-Cota, Gloria; Hortelano-Moncada, Yolanda; Briones-Salas, Miguel (THERYA, 2018)
The bat, Myotis occultus (Vespertilionidae) is a rare and small-sized bat. The known distribution of M. occultus extends from the semi-arid areas of the southwestern United States down as far as the middle half of Mexico, not having beeing previously registered in the state of Guanajuato in Mexico. In August 2008 and February 2013, we collected bats using mist nets in the locality of Llanos de Santa Ana located within the municipality of Guanajuato, Gto., Mexico. We collected twelve specimens of M. occultus at the entrance of an abandoned mine in the municipality of Guanajuato, which represents the first documented record of the species in Guanajuato and confirms its presence for the state as predicted by potential distribution maps of the species. It is a small-sized bat, with few records in Mexico and, according to previous studies, its distribution is confirmed for the states of Chihuahua, Zacatecas, Mexico State, Mexico City, and now Guanajuato.